Republic of Kazakhstan : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
The paper provides information on recent economic developments in Kazakhstan. Adoption of the new budget system law was an important step toward a more transparent and stable system of intergovernmental fiscal relations in Kazakhstan. Good progress has been made by the government to implement the key elements of the legal framework for an efficient financial sector. The paper focuses on two of the shocks, the fall in the terms of trade and the real effective appreciation of the Tenge. The statistical data are also presented.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet